Spatial Multi Criteria Analysis for Evaluation of Residential Land in South Jambi, Jambi City - Hermawan Setiawan (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Lingungan Hidup, 2024)
The land is a landscape on the earth's surface, dynamic to changes, such as converting to settlements. Settlement is driven by changes in population, the greater the population, the greater the need for land to be converted into housing. Based on data from 2018 to 2022, there has been an increasing population in the South Jambi sub-district, which is a strong indication of residential development. This research aims to evaluate the suitability of settlements in the South Jambi sub-district in 2022, using five variables namely, distance from the road, distance from the river, slope, soil type, and flood hazard index. The method of analysis uses the Spatial Multi-Criteria Analysis (SMCA) method. The research results show that the South Jambi sub-district is dominated by the suitable criteria of 568.0 hectares or 86.4%, very suitable criteria obtain 5.8 hectares or 0.9%, and somewhat suitable areas of 80.8 hectares or 12.3%. This means that the South Jambi area has a relatively high level of suitability for settlement. It is hoped that these results can provide information for various stakeholders in determining areas that are suitable for residential development, especially those that are at risk of flooding.